Excess maternal salt or fructose intake programmes sex-specific, stress- and fructose-sensitive hypertension in the offspring. Issue 4 (10th December 2015) - Gray, Clint; Gardiner, Sheila M.; Elmes, Matthew; Gardner, David S.
Abstract: The Western diet is typically high in salt and fructose, which have pressor activity. Maternal diet can affect offspring blood pressure, but the extent to which maternal intake of excess salt and fructose may influence cardiovascular function of the offspring is unknown. We sought to determine the effect of moderate maternal dietary intake of salt and/or fructose on resting and stimulated cardiovascular function of the adult male and female offspring. Pregnant rats were fed purified diets (±4 % salt) and water (±10 % fructose) before and during gestation and through lactation. Male and female offspring were weaned onto standard laboratory chow. From 9 to 14 weeks of age, cardiovascular parameters (basal, circadian and stimulated) were assessed continuously by radiotelemetry. Maternal salt intake rendered opposite-sex siblings with a 25-mmHg difference in blood pressure as adults; male offspring were hypertensive (15 mmHg mean arterial pressure (MAP)) and female offspring were hypotensive (10 mmHg MAP) above and below controls, respectively. Sex differences were unrelated to endothelial nitric oxide activity in vivo, but isolation-induced anxiety revealed a significantly steeper coupling between blood pressure and heart rate in salt-exposed male offspring but not in female offspring. MAP of all offspring was refractory to salt loading but sensitive to subsequent dietary fructose, an effect exacerbated in female offspring from fructose-fed dams. Circadian analyses of pressure in all offspring revealed higher mean set-point for heart rate and relative non-dipping of nocturnal pressure. In conclusion, increased salt and fructose in the maternal diet has lasting effects on offspring cardiovascular function that is sex-dependent and related to the offspring's stress–response axis.